2018
DOI: 10.3390/s18082549
|View full text |Cite
|
Sign up to set email alerts
|

Accurate Indoor Localization Based on CSI and Visibility Graph

Abstract: Passive indoor localization techniques can have many important applications. They are nonintrusive and do not require users carrying measuring devices. Therefore, indoor localization techniques are widely used in many critical areas, such as security, logistics, healthcare, etc. However, because of the unpredictable indoor environment dynamics, the existing nonintrusive indoor localization techniques can be quite inaccurate, which greatly limits their real-world applications. To address those problems, in this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 33 publications
0
24
0
Order By: Relevance
“…This work yields an error distance of 0.95 m with a single access point. Authors in [27] used a visibility graph to transform the CSI amplitude and phase information of individual sub-carriers into complex networks extracting the network features accordingly. Then, machine learning algorithms are applied to infer the locations, yielding a 96% accuracy.…”
Section: Related Workmentioning
confidence: 99%
“…This work yields an error distance of 0.95 m with a single access point. Authors in [27] used a visibility graph to transform the CSI amplitude and phase information of individual sub-carriers into complex networks extracting the network features accordingly. Then, machine learning algorithms are applied to infer the locations, yielding a 96% accuracy.…”
Section: Related Workmentioning
confidence: 99%
“…Support vector regression (SVR) based system was introduced in [24] for device-free localization which [25], [26] also considered. There are other various learning techniques for localization, such as autoencoder [27], clustermapping (C-Map) [28], kNN [29], multi-layer perceptron (MLP), [30], canonical correlation analysis (CCA) [31], and visibility graph (VG) [32].…”
Section: Related Workmentioning
confidence: 99%
“…However, the accurately calibration of Wi-Fi fingerprints remains a question due to the inherent instability of the real world. Recently, channel state information (CSI) based indoor localization [36,37] have attracted much attention. When compared with RSS-based solution, CSI maintains more stability and sensitivity, which can provide detailed and fine-grain subcarrier information.…”
Section: Introductionmentioning
confidence: 99%
“…When compared with RSS-based solution, CSI maintains more stability and sensitivity, which can provide detailed and fine-grain subcarrier information. For example, in [36], a CSI based indoor localization technique is developed by employing both the intrasubcarrier statistics features and the inter-subcarrier network features. Their results showed that it could achieve 96% classification accuracy.…”
Section: Introductionmentioning
confidence: 99%